Design and implementation of LTCC coreless transformers for intelligent solid-state switch. (December 2022) - Lu, Yufang; Huang, Zhiai; Chen, Chunhai; Tang, Haihua; Shi, Lei; Zhuang, Yiqi
Abstract: This paper designs, manufactures, and evaluates a multilayer coreless low temperature coiffed ceramic (LTCC) transformer for solid state power controller (SSPC) applications. A series of circular spiral transformers with different layers and turns are fabricated in 2 ∼ 6 layers LTCC. The transformers are simulated and analyzed by using simulation software HFSS, in which the analysis results can be used for the design basis of transformers. The comparison results of these different transformers in terms of resistance, self-loss, Q-factor, mutual inductance, coupling coefficient, and energy efficiency are presented. The working area of the best performance of these transformers for SSPC application is determined, and the IDU used in SSPC implementation based on LTCC coreless transformer is completed.